A behavioral approach to sexual function: testing a moderation mediation model with expression of feelings, sexual self-disclosure and gender. Issue 6 (18th August 2022) - Sukhanova, Anna; Pascoal, Patrícia M.; Rosa, Pedro J.
Abstract: Little is known about specific intimacy dimensions' role in sexual function. In the current study, we aimed to gain more insight into how expression of feelings and sexual self-disclosure (a mediator) might potentially affect sexual functioning testing a theoretically based moderated mediation model, that uses gender as a moderator. A total of 661 participants, of which 211 were men (31, 90%) and 450 were women (68, 10%) aged 18-74 years involved in a monogamous committed relationship participated in the study. We used macro PROCESS 3.2 for IBM – SPSS to test simple mediation and moderated mediation models. The data revealed a significant overall effect of expression of feelings on sexual function, supporting that sexual self-disclosure mediates this relationship. We found that gender does not moderate either the relationship between expression of feelings and sexual self-disclosure nor the trajectory between sexual self-disclosure and sexual function. Our results highlight the importance of taking an interpersonal behavioral approach to sexual function, namely one that focuses on communication behaviors. However, these results need to be explored with clinical samples to understand their full potential for clinical interventions within a behavioral paradigm to partnered people's sexual problems.